Association Between Copeptin and Six-Month Neurologic Outcomes in Patients With Moderate Traumatic Brain Injury - Jeon, Jin Pyeong; Kim, Seonghyeon; Kim, Tae Yeon; Han, Sung Woo; Lim, Seung Hyuk; Youn, Dong Hyuk; Kim, Bong Jun; Hong, Eun Pyo; Park, Chan Hum; Kim, Jong-Tae; Ahn, Jun Hyong; Rhim, Jong Kook; et al. (Frontiers in Neurology, 2022)
Background: Copeptin has been reported as a prognostic biomarker in traumatic brain injury (TBI). However, most of the previous studies analyzed the outcomes of patients with severe TBI. We aimed to investigate the prognostic significance and the precise predictive value of copeptin in assessing the neurologic outcome following moderate TBI. Methods: Patients were prospectively enrolled between May 2017 and November 2020. We consecutively measured plasma copeptin within 24 hours, and days 3, 5, and 7 after trauma using ELISA. The primary objective was to correlate plasma copeptin levels with poor neurologic outcomes at 6 months after moderate TBI. The secondary objective was to compare the prognostic accuracy of copeptin and C-reactive protein (CRP) in assessing patients’ outcomes. Results: A total of 70 patients were included in the final analysis. Twenty-nine patients (41.4%) showed a poor neurologic outcome at 6 months. Multivariable logistic regression analysis revealed that increased copeptin (OR=1.020, 95% CI: 1.005-1.036), Glasgow Coma Scale score of 9 or 10 (OR=4.507, 95% CI: 1.266-16.047), and significant abnormal computed tomography findings (OR=4.770; 95% CI: 1.133-20.076) were independent risk factors for poor outcomes. Consecutive plasma copeptin levels were significantly different and correlated with the outcomes (p<0.001). Copeptin on day 7 exhibited better prognostic performance than CRP in predicting 6-month poor outcomes, with an AUROC difference of 0.179 (95% CI: 0.032-0.325). Conclusion: Plasma copeptin level can be a useful prognostic biomarker for predicting 6-month outcomes in patients with moderate TBI.